Improvement of Mechanical and Fatigue Properties for Aluminum Alloy 7049 By Using Nano Composites Technique - M., Alalkawi H. J.; Khenyab, Ali Yousuf K; Ali, Abduljabar H. (Al-Khwarizmi Engineering Journal, 2019)
The aim of present work is to improve mechanical and fatigue properties for Aluminum alloy7049 by using Nano composites technique. The ZrO2 with an average grain diameter of 30-40 nm, was selected as Nano particles, to reinforce Aluminum alloy7049 with different percentage as, 2, 4, 6 and 7 %. The Stir casting method was used to fabricate the Nano composites materials due to economical route for improvement and processing of metal matrix composites. The experimental results were shown that the adding of zirconium oxide (ZrO2) as reinforced material leads to improve mechanical properties. The best percentage of improvement of mechanical properties of 7049 AA was with 4% wt. of ZrO2 about (7.76% ) for ultimate tensile stress UTS, (9.62% ) for yield stress YS and (9.92%) for hardness HB than other of adding of 2, 6 and 7% of ZrO2. Also the results shown that the fatigue strength of 7049 AA with 4 % ZrO2 nanoparticles is higher than that of 7049 AA under constant loading 9.86% at 108 cycles as well as the fatigue life factor (IFLF %) at different amplitude stress 400, 350, 300 and 250 MPa  was improvement in range 66, 115, 63 and 107%  respectively.